Ultrastructural Characteristics of Gallbladder Epithelial Inclusions Mimicking Cystoisospora: Further Evidence Bringing Closure to the Cystoisospora Controversy. Issue 1 (10th October 2019) - Gopinath, Arun; Mubeen, Aysha; Baskovich, Brett; Ginn, Amber; Shukri, Amal; Menes, Manual; Kenneth, Keyler; Makary, Raafat; Herrera, Guillermo A; Masood, Shahla; Alkhasawneh, Ahmad
Abstract: Objectives: There is recently reported increased prevalence of Isospora organisms in cholecystectomy specimens from immunocompetent patients, especially in acalculous cholecystectomies. We performed an ultrastructural and molecular evaluation of these specimens. Methods: From 28 gallbladders with intraepithelial inclusions, two specimens with diffuse involvement of the gallbladder epithelium were analyzed by electron microscopy. Polymerase chain reaction was performed on five samples for the ITS2 region of C belli and eukaryotic 18S region. The 18S products were sequenced by next-generation sequencing. Results: Electron microscopic analysis showed cytoplasmic condensations leading to vacuole formation. In contrast with true C belli, there were no identifiable organelles or organization. None of these cases showed amplified products other than human on molecular analysis. Conclusions: Electron microscopic analysis demonstrates that the inclusions are condensed cytoplasmic material and not true organisms.